Associação entre os níveis de fator de necrose tumoral alfa e interferon gama e gravidade da bronquiolite viral aguda : revisão sistemática e metanalise - Dias, Carolina Frizzera (2019)
Acute bronchiolitis caused by the respiratory syncytial virus triggers an inflammatory response with the production and release of several proinflammatory cytokines including the tumor necrosis factor alpha (TNF-a) and interferon gamma (IFN-g). Evidence suggests that their levels are associated with the severity of the infection. This systematic review and meta-analysis aim to assess whether the levels of TNF-a and IFN-g are associated with the severity of acute viral bronchiolitis. We searched MEDLINE libraries (via PUBMED), EMBASE, Cochrane Central Register of Controlled Trials (CENTRAL), Scientific Electronic Library Online (SciELO), Latin American Caribbean Health Sciences Literature (LILACS), Cumulative Index to Nursing and Allied Health Literature (CINAHL), Web of Science, and the gray literature through April 2020. Random effect models were used for general and subgroup analysis. In total, six studies were included with a total of 744 participants. The mean TNF-a levels between the severe group did not differ from the control group 0.14 (95% CI: -0.53 to 0.82, I2 = 91%, p <0.01); the heterogeneity was high. The results remained insignificant when the analyses were performed including only studies with high quality 0.25 (95% CI: -0.46 to 0.96, I2 = 92%, p <0.01) I2 = 95%, p = 0.815), when TNF-a was nasal 0.60 (95% CI: -0.49 to 1.69), I2 = 94%, p <0.01), or serum -0.08 (95% CI: - 0.48 to 0.31), I2 = 29%, p = 0.24). In the analysis of studies measuring IFN-g, there was also no significance of -0.67 (95% CI: -1.56 to 0.22, I2 = 76%, p = 0.04). In conclusion, this meta-analysis suggests that the most severe patients do not have different mean TNF-a and IFN-g values than patients with mild disease, but the heterogeneity of the studies was high.